A meta-analysis of genome-wide studies of resilience in the German population - Herrera-Rivero, Marisol; Garvert, Linda; Horn, Katrin; Löbner, Margrit; Weitzel, Elena Caroline; Stoll, Monika; Lichtner, Peter; Teismann, Henning; Teumer, Alexander; Van der Auwera, Sandra; Völzke, Henry; Völker, Uwe; et al. (Molecular psychiatry, 2025)
Resilience is the capacity to adapt to stressful life events. As such, this trait is associated with physical and mental functions and conditions. Here, we aimed to identify the genetic factors contributing to shape resilience. We performed variant- and gene-based meta-analyses of genome-wide association studies from six German cohorts (N = 15822) using the 11-item version of the Resilience Scale (RS-11) as outcome measure. Variant- and gene-level results were combined to explore the biological context using network analysis. In addition, we conducted tests of correlation between RS-11 and the polygenic scores (PGSs) for 12 personality and mental health traits in one of these cohorts (PROCAM-2, N = 3879). The variant-based analysis found no signals associated with resilience at the genome-wide level (p < 5 × 10−8), but suggested five genomic loci (p < 1 × 10−5). The gene-based analysis identified three genes (ROBO1, CIB3 and LYPD4) associated with resilience at genome-wide level (p < 2.48 × 10−6) and 32 potential candidates (p < 1 × 10−4). Network analysis revealed enrichment of biological pathways related to neuronal proliferation and differentiation, synaptic organization, immune responses and vascular homeostasis. We also found significant correlations (FDR < 0.05) between RS-11 and the PGSs for neuroticism and general happiness. Overall, our observations suggest low heritability of resilience. Large, international efforts will be required to uncover the genetic factors that contribute to shape trait resilience. Nevertheless, as the largest investigation of the genetics of resilience in general population to date, our study already offers valuable insights into the biology potentially underlying resilience and resilience’s relationship with other personality traits and mental health.
Online veröffentlicht: 08. August 2024
Gesehen am 04.11.2024